ANALISA KLASIFIKASI C4.5 TERHADAP FAKTOR PENYEBAB MENURUNNYA PRESTASI BELAJAR MAHASISWA PADA MASA PANDEMI (Studi Kasus : MAHASISWA TEKNIK INFORMATIKA UNIVERSITAS PAMULANG) - Nanda Noverdi Ruziki; Ahmad Fikri Zulfikar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
At the end of 2019 there was an outbreak that shook the world, the outbreak was known as Covid19. In this case, many activities outside the home must be limited, even every time we want to go out, we are required to wear a mask and keep our distance. The Ministry of Education made a policy that teaching and learning activities must be carried out online or online to prevent the wider spread of Covid-19. But in the implementation of not going smoothly, there must be problems that can occur, namely problems such as students not understanding the material presented by the lecturer, the home factor that is not conducive to participating in online learning, health factors that affect learning. The purpose of this study was to determine the factors causing the decline in student learning achievement during the pandemic using the C4.5 method. The source of the data obtained by distributing questionnaires online to informatics engineering students of Pamulang University. In this study, there are five criteria for factors that influence the factors that cause the decline in student learning achievement during a pandemic, namely: physical factors, psychological factors, family factors, college factors, community factors. From the results of the calculation, family factors are the factors that most influence the factors that cause the decline in student learning achievement. This research was conducted using the help of RapidMiner software and obtained an accuracy value of 90.00%.